Analysis of outcomes for children examined in the outpatient clinic of tertiary care pediatric institution due to loss of consciousness - Peličić Milena; Petrić Milica; Pešterac Anika; Vučetić-Tadić Biljana (Medicinski Podmladak)
Introduction: Loss of consciousness is a common anamnestic data in pediatric outpatient clinics. Aim: To determine the outcome for children who were examined due to loss of consciousness in the outpatient clinic of a tertiary care pediatric institution during a two-and-a-half-month period. Material and methods:A descriptive study was conducted. Data were obtained from the medical records of the outpatient department in the Institute for Mother and Child Protection of Serbia "Dr. Vukan Čupić", in the admission period from September 3 until November 17 2022. Considered data were the following: gender, age, referral and discharge diagnosis, nature of the attack on admission, associated complaints and comorbidities, conducted EEG (electroencephalography) and CT (computerized tomography)/MRI (magnetic resonance imaging) imaging, prescribed therapy and outcome. All data were processed in SPSS v21. Results: The study included 97 patients (50 male and 47 female) with an average age of 96 months. The most common referral diagnosis were unclassified convulsions (33%), and discharge diagnosis was syncope (32%). In 49.5% of cases, seizures were reported as the first episode. Elevated body temperature, as the most common associated symptom, was present in 32% of patients. Comorbidities were found in 10.3% of patients. Only 49.5% of patients were referred for home treatment, 46.4% were hospitalized, 2% were referred for subspecialty examination. Therapeutically, advice was most often given for syncope (37%), while Diazepam or Midazolam were most often prescribed medicines to stop attacks (27.1%). The EEG was performed in 10.3% of patients, of which 3.1% were normal and 4.1% pathological findings. Also, CT/MRI scans were performed in 9.3% of patients and all had normal findings. Conclusion: The majority of children who experience loss of consciousness have a favorable outcome - complete recovery, without neurological deficits and complications, and are discharged home without continuous therapy, with advice for preventing the recurrence of complaints.